Intermolecular interactions and structural organization of a native chitin-chitosan hydrocolloid network resolved by solid-state NMR and molecular dynamics - Qinghui Cheng; Chunyan Lu; Xiufang Gong; Qingyan Wang; Siming Liao; Lihua Chen (Food Hydrocolloids, 2026)

Flexible wave energy technologies: A systematic review of advances, challenges, and prospects - Qing Lu; Siming Zheng; Adi Kurniawan; Xun Meng; Hongda Shi; Martyn Hann; Deborah Greaves (Ocean Engineering, 2026)

A hierarchical hybrid flood modeling framework: deconstructing runoff response into initiation states and generation processes - Tao Xie; Lu Chen; Bin Yi; Zhiyuan Leng; Siming Li; Yazhong Wu; Deming Zhu (Journal of Hydrology, 2026)

Corrigendum to “A flood peak prediction in data-scarce mountain river basins considering the time distribution of rainfall” [J. Hydrol. 673 (2026) 135352] - Siming Li; Lu Chen; Binlin Yang; Bin Yi; Zhiyuan Leng; Tao Xie; Yang Song (Journal of Hydrology, 2026)

A flood peak prediction in data-scarce mountain river basins considering the time distribution of rainfall - Siming Li; Lu Chen; Binlin Yang; Bin Yi; Zhiyuan Leng; Tao Xie; Yang Song (Journal of Hydrology, 2026)

Scalable fabrication of ultrathin LiIn@Cu composite anodes via roll-to-roll dip coating for high-energy-density batteries - Qihang Zhang; Anli Wang; Yifei Chen; Zihan Lin; Changyi Dong; Qiang Lu; Jixian Lv; Weike Yu; Siming Yang; Xiaoqun Qi; Jia Li; Fei Shen; et al. (Chemical Engineering Journal, 2026)

Experimental study on time-dependent behavior of partially prestressed concrete beams: Coupled effects of creep, cracking, and prestress loss - Weiqiang Guo; Ya Wei; Siming Liang; Yiwen Lu (Engineering Structures, 2026)

Optimization on escape exit selection for personnel in highway tunnel fires - Jinghong Wang; Jintao Li; Hongcheng Lu; Siming Wang; Ran Ye; Jialin Wu (Tunnelling and Underground Space Technology, 2026)

Revealing long-term runoff mechanisms using the deep learning model interpretable framework driven by global and local information - Binlin Yang; Lu Chen; Siming Li; Bin Yi; Nengjie Hu (Journal of Hydrology, 2025)

A Dynamic Time-varying Distributed Unit Hydrograph Considering the Heterogeneity of Runoff Generation - Bin Yi; Lu Chen; Binlin Yang; Zhiyuan Leng; Siming Li; Tao Xie (Water Resources Management, 2025)

The role of lactate metabolism in retinoblastoma tumorigenesis and ferroptosis resistance - Zhihui Zhang; Junjie Tang; Yaoming Liu; Yinghao Wang; Jinmiao Li; Yang Gao; Chao Cheng; Shicai Su; Shuxia Chen; Siming Ai; Ping Zhang; Rong Lu (Tissue and Cell, 2025)

Wheat bran insoluble fiber with varying particle distributions orchestrates microbial metabolism to counteract obesity and hyperlipidemia - Kexin Niu; Bingqian Yang; Lu Gan; Meng Niu; Kaikai Li; Siming Zhao (Food Bioscience, 2025)

Prediction of near-surface conditions following the 2023/24 sudden stratospheric warming by the S2S project models - Jian Rao; Xiaoqi Zhang; Qian Lu; Siming Liu (Atmospheric Research, 2025)

Brazilin alleviates acute lung injury via inhibition of ferroptosis through the SIRT3/GPX4 pathway - Xiaopei Yan; Li Xu; Chang Qi; Yiling Chang; Juanjuan Zhang; Ning Li; Baoyu Shi; Bo Guan; Siming Hu; Chao Huang; Hui Wang; Ying Chen; et al. (Apoptosis, 2025)

Evaluating the wilderness status of long-distance trails in the United States - Exploring the potential of SDGSAT-1 glimmer imager data - Liding Wang; Mingyang Lv; Changyong Dou; Yue Cao; Steve Carver; Xiancai Lu; Shaochun Dong; Siming Deng; Huadong Guo (Remote Sensing of Environment, 2025)

Evaluating the impact of improved filter-wrapper input variable selection on long-term runoff forecasting using local and global climate information - Binlin Yang; Lu Chen; Bin Yi; Siming Li (Journal of Hydrology, 2024)

CO prodrugs: a new scaffold of adamantane-fused norbornen-7-ones with tunable water solubility - Ce Yang; Xingyue Ji; G. S. Sainaga Jyothi Vaskuri; Xiaoxiao Yang; Wen Lu; Zhengnan Yuan; Dongning Liu; Siming Wang; Chalet Tan; Binghe Wang (Medicinal Chemistry Research, 2024)

Anticancer effect of hUC-MSC-derived exosome-mediated delivery of PMO-miR-146b-5p in colorectal cancer - Siming Yu; Ran Liao; Lu Bai; Madi Guo; Yu Zhang; Yumin Zhang; Qi Yang; Yushuai Song; Zhiwei Li; Qingwei Meng; Shubin Wang; Xiaoyi Huang (Drug Delivery and Translational Research, 2024)
Antisense oligonucleotide (ASO) is a novel therapeutic platform for targeted cancer therapy. Previously, we have demonstrated that miR-146b-5p plays an important role in colorectal cancer progression. However, a safe and effective strategy for delivery of an ASO to its targeted RNA remains as a major hurdle in translational advances. Human umbilical cord mesenchymal cell (hUC-MSC)–derived exosomes were used as vehicles to deliver an anti-miR-146b-5p ASO (PMO-146b). PMO-146b was assembled onto the surface of exosomes (e) through covalent conjugation to an anchor peptide CP05 (P) that recognized an exosomal surface marker, CD63, forming a complex named ePPMO-146b. After ePPMO-146b treatment, cell proliferation, uptake ability, and migration assays were performed, and epithelial-mesenchymal transition progression was evaluated in vitro. A mouse xenograft model was used to determine the antitumor effect and distribution of ePPMO-146b in vivo. ePPMO-146b was taken up by SW620 cells and effectively inhibited cell proliferation and migration . The conjugate also exerted antitumor efficacy in a xenograft mouse model of colon cancer by systematic administration, where PPMO-146b was enriched in tumor tissue. Our study highlights the potential of hUC-MSC-derived exosomes anchored with PPMO-146b as a novel safe and effective approach for PMO backboned ASO delivery. Graphical Abstract Schematic illustration of the preparation of an exosomal anchor peptide (CP05)-PMO that conjugately binds to exosomes from hUC-MSCs (ePPMO-146b) and the antitumor effect of ePPMO-146b in CRC, which occurs through the inhibition of Smad signaling and epithelial–mesenchymal transition.

A new Cd(II) Complex: Fluorescence Performances, Loading with Budesonide-hydrogels on Pediatric Asthma and Molecular Docking - Lu Luo; Siming Gong; Lin Lei; Xin Yu; Shimin Zhong (Journal of Fluorescence, 2024)

Isoalantolactone relieves depression-like behaviors in mice after chronic social defeat stress via the gut-brain axis - Siming Wang; Qihan Cai; Lu Xu; Yanan Sun; Mengmeng Wang; Yu Wang; Lili Zhang; Keqing Li; Zhiyu Ni (Psychopharmacology, 2023)
Rationale The management of depression continues to be challenging despite the variety of available antidepressants. Herbal medicines are used in many cultures but lack stringent testing to understand their efficacy and mechanism of action. Isoalantolactone (LAT) from Elecampane ( Inula helenium ) improved the chronic social defeat stress (CSDS)-induced anhedonia-like phenotype in mice comparable to fluoxetine, a selective serotonin reuptake inhibitor (SSRI). Objectives Compare the effects of LAT and fluoxetine on depression-like behaviors in mice exposed to CSDS. Result The CSDS-induced decrease in protein expression of postsynaptic density (PSD95), brain derived neurotrophic factor (BDNF), and glutamate receptor subunit-1 (GluA1) in the prefrontal cortex was restored by LAT. LAT showed robust anti-inflammatory activity and can lessen the increase in IL-6 and TNF-α caused by CSDS. CSDS altered the gut microbiota at the taxonomic level, resulting in significant changes in α- and β-diversity. LAT treatment reestablished the bacterial abundance and diversity and increased the production of butyric acid in the gut that was inhibited by CSDS. The levels of butyric acid were negatively correlated with the abundance of Bacteroidetes , and positively correlated with those of Proteobacteria and Firmicutes across all treatment groups. Conclusions The current data suggest that, similar to fluoxetine, LAT show antidepressant-like effects in mice exposed to CSDS through the modulation of the gut-brain axis.

The in-situ dextran produced in rice protein yogurt: Effect on viscosity and structural characteristics - Yu Lu; Caihua Jia; Meng Niu; Yan Xu; Siming Zhao (Carbohydrate Polymers, 2023)

Global DNA and protein interactomes of FLT1P1 (Fms-related tyrosine kinase 1 pseudogene 1) revealed its molecular regulatory functions associated with preeclampsia - Lu Zhao; Siming Xin; Yunfei Wu; Shaofang Huang; Kangxiang Xu; Yuqi Xu; Dong Ruan; Bingqi Wu; Dong Chen; Xiaoju He (Molecular Biology Reports, 2023)

Supplementation of Bacillus sp. DU-106 Alleviates Antibiotic-Associated Diarrhea in Association with the Regulation of Intestinal Microbiota in Mice - Darong Huang; Yanlan Chen; Hongzhu Chen; Xinyu Deng; Jianzhao Huang; Siming Lu; Pan Li; Bing Du (Probiotics and Antimicrobial Proteins, 2022)

Genetic parameters for growth and wood mechanical properties in Eucalyptus cloeziana F. Muell. - Changrong Li; Qijie Weng; Jian-Bo Chen; Mei Li; Changpin Zhou; Shengkan Chen; Wei Zhou; Dongqiang Guo; Cuixiang Lu; Jian-Cheng Chen; Dongyun Xiang; Siming Gan (New Forests, 2017)

Distribution and linkage disequilibrium analysis of polymorphisms of GH1 gene in different populations of pigs associated with body size - YUNYUN CHENG; SONGCAI LIU; DAN SU; CHAO LU; XIN ZHANG; QINGYAN WU; SIMING LI; HAOYU FU; HAO YU; LINLIN HAO (Journal of Genetics, 2016)

Up-regulation of SKIP relates to retinal ganglion cells apoptosis after optic nerve crush in vivo - Yu Wu; Fan Xu; Hui Huang; Lifei Chen; Meidan Wen; Li Jiang; Lu Lu; Li Li; Di Song; Siming Zeng; Li Li; Min Li (Journal of Molecular Histology, 2014)

A new acorane sesquiterpene from the aerial parts of Psychotria yunnanensis - Qinpei Lu; Junsong Wang; Jun Luo; Xiaobing Wang; Siming Shan; Lingyi Kong (Natural Product Research, 2014)

Upregulation of Gem relates to retinal ganglion cells apoptosis after optic nerve crush in adult rats - Fan Xu; Hui Huang; Yu Wu; Lu Lu; Li Jiang; Lifei Chen; Siming Zeng; Li Li; Min Li (Journal of Molecular Histology, 2014)